1988
DOI: 10.1172/jci113591
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin synthesis by small cell lung cancer cells acts as an autocrine regulator of cellular proliferation.

Abstract: Since transferrin is required for cellular proliferation, we investigated transferrin synthesis by a small cell lung cancer line (NCI-H510) that survives in serum-free media without added transferrin. Immunoassays for human transferrin demonstrated that these cells contained immunoreactive human transferrin. Immunofluorescence studies showed that the protein is expressed on the surface of cells, presumably bound to transferrin receptor. Media conditioned by NCI-H510 cells support proliferation of human leukemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(44 citation statements)
references
References 24 publications
1
41
1
1
Order By: Relevance
“…It has been demonstrated that transferrin synthesis by SCLC acts as an autocrine regulator of cellular proliferation (Vostrejs et al, 1988). Immunohistochemical staining for transferrin receptor, which is needed for internalization of transferrin and iron, has been used most extensively for measuring the proliferation rate of cells and is thought to be of some prognostic value in several types of malignant tumours.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that transferrin synthesis by SCLC acts as an autocrine regulator of cellular proliferation (Vostrejs et al, 1988). Immunohistochemical staining for transferrin receptor, which is needed for internalization of transferrin and iron, has been used most extensively for measuring the proliferation rate of cells and is thought to be of some prognostic value in several types of malignant tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Transferrin is considered to be an conditioned medium; rO, BC47 supplemented with 10% conditioned medium and anti-transferrin antibody (20 ,ug ml-'); A, BC47 supplemented with anti-human IgG; and *, KU7 supplemented with anti-transferrin antibody (20 jg ml-') autocrine regulator of cell proliferation in malignant tumour cells, where it may also be largely responsible for acquisition of serum independence (Vostrejs et al, 1988;Shapiro and Wagner, 1989). Growth factors exert their mitogenic effect by interaction with specific cell surface receptors on responsive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Specialized cellular proliferation may be limited by insufficient delivery of transferrin-bound iron from plasma during situations when iron is being withheld from the circulation. To evade the difficulty of obtaining iron, certain malignant cells have the ability to produce the 'transferrin-like' substance (Kitada and Hays, 1985;Morrone et al, 1988;Dittman and Petrides, 1991;Gruber et al, 1993) as well as native serum transferrin (Vostrejs et al, 1988;Vandewalle et al, 1989;Ohkawa et al, 1990;Stackpole et al;. It could be hypothesized, therefore, that the capability of a specific subset of human bladder carcinomas to synthesize transferrin and/or a 'transferrin-like' substance might provide a source of available iron to support localized proliferation of bladder carcinoma cells in vivo in areas not well vascularized.…”
Section: Discussionmentioning
confidence: 99%
“…Transferrin is also present in placenta, kidney, mammary glands, stomach, immune system cells, heart, lungs and tumor cells in detectable amounts [74][75][76][77][78]. The expression level of Trf receptor on the surface of proliferating cells is higher when compared to the absent or rare expression of Trf receptor on the surface of resting cells [79].…”
Section: Salivary Transferrin As a Molecular Markermentioning
confidence: 99%